1985
DOI: 10.1200/jco.1985.3.6.818
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized comparison of epirubicin and doxorubicin in patients with advanced breast cancer.

Abstract: Fifty-four patients with advanced breast cancer who had failed prior non-anthracycline combination chemotherapy were randomized to treatment with either epirubicin 85 mg/m2 or doxorubicin 60 mg/m2 intravenously every three weeks. Of 52 evaluable patients, 25% (six of 24) treated with epirubicin, and 25% (seven of 28) treated with doxorubicin experienced major therapeutic responses. The median duration of response to epirubicin was 11.9 months compared to 7.1 months with doxorubicin. Cardiotoxicity was monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
7

Year Published

1989
1989
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(77 citation statements)
references
References 17 publications
2
68
0
7
Order By: Relevance
“…Epirubicin reportedly had lower cardiotoxicity compared with doxorubicin on the basis of a mg/m 2 cumulative dose. 13 In a large retrospective analysis, Ryberg et al reported estimated CHF risks of 0.6% and 14.5% at cumulative doxorubicin doses of 550 mg/m 2 and 1000 mg/m 2 , respectively. 14 However, a long-term prospective trial 15 showed that patients who received high cumulative doses of epirubicin (850 -1000 mg/m 2 ) had a risk of CHF that increased over a 5-year period (11% at 1 year, 20% at 5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Epirubicin reportedly had lower cardiotoxicity compared with doxorubicin on the basis of a mg/m 2 cumulative dose. 13 In a large retrospective analysis, Ryberg et al reported estimated CHF risks of 0.6% and 14.5% at cumulative doxorubicin doses of 550 mg/m 2 and 1000 mg/m 2 , respectively. 14 However, a long-term prospective trial 15 showed that patients who received high cumulative doses of epirubicin (850 -1000 mg/m 2 ) had a risk of CHF that increased over a 5-year period (11% at 1 year, 20% at 5 years).…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity, however, was generally more pronounced in the doxorubicintreated patients. The four other studies compared the two drugs on an expected equimyelotoxic basis with doses of epirubicin ranging from 1.4 to 1.5 times the dose of doxorubicin (Jain et al, 1985;Taguchi et al, 1986;Hortobagyi et al, 1989;Perez et al, 1991). Similarly none of these studies showed significant differences in response rates, duration of response or survival between the two treatment arms.…”
Section: Discussionmentioning
confidence: 99%
“…As with doxorubicin, the incidence of epirubicin-induced cardiac failure is greatly dependent on the cumulative dose of epirubicin, but it depends also on other factors, such as the mode of administration of epirubicin, concomitant medication, presence of previous cardiac disease, amount of cardiac irradiation and individual and unrecognized factors. Congestive cardiac failure is rare at cumulative epirubicin doses less than 1000 mg m -2 in patients without known risk factors for cardiac failure (Jain et al, 1985;Dardir et al, 1989;Nielsen et al, 1990). However, no studies have yet addressed the clinical significance of subclinical cardiac damage, which may be a highly relevant issue in the long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%